Implementasi Program Jaminan Kecelakaan Kerja (Jkk) PadaBPJS Ketenagakerjaan Terhadap Pekerja Di PT PentasariPranakarya Semarang - Arumsari Dhamayanti, Putri, Shallman Al Farizi, SH, M.kn, Inayah, S.H, M.H (2017)
In Indonesia, a limited liability company that can provide opportunities for people to get a job and already has a lot of manpower, one of which is PT. Pentasari Pranakarya. PT. Pentasari Pranakarya. The company is engaged in rubber and tire industry, including general marketing, export, import, and local marketing. Companies especially PT. Pentasari Pranakarya in conducting production activities will not be able to produce a production without workers, there are three (3) types, namely workers, contract workers, permanent workers (in the factory), and parttime workers. By working at PT. Pentasari Pranakarya timbulah relationship between labor (workers) with employers, namely PT. Pentasari Pranakarya where it contains rights and obligations are reciprocal, one of the obligations of employers that guarantees the protection of labor. This research uses descriptive normative approach method with primary and secondary data. The data are collected through the study of literature, documentation, questionnaire, and interview using qualitative data analysis. Based on the results of research and discussion that has been done can be concluded that the implementation of labor protection guarantee in PT. Pentasari Pranakarya Semarang only for accident insurance (JKK), if there is a labor of PT. Pentasari Pranakarya Semarang injured at work, the workers injured at work it will first seek treatment from a doctor or the nearest hospital and then the fee in klaimkan to BPJS Employment